The Kissing hand - Penn, Audrey, 1947-; Harper, Ruth E.; Leak, Nancy M. (Terre Haute, IN : Tanglewood Press, 2007)
Chester the raccoon is reluctant to go to kindergarten for the first time, but his mother teaches him a secret way to carry her love with him. Includes an audio CD.
Compact disc.
3.0
K-3.
K-3
Keywords: Forest animals -- Juvenile fiction; Kindergarten -- Juvenile fiction; Mothers and sons -- Juvenile fiction; Raccoon -- Juvenile fiction; Schools -- Juvenile fiction; Separation anxiety -- Juvenile fiction; Forest animals -- Fiction; Kindergarten -- Fiction; Mothers and sons -- Fiction; Raccoon -- Fiction; Schools -- Fiction; Separation anxiety -- Fiction; Audiobooks, English; Forest animals -- Fiction; Kindergarten -- Fiction; Mother-son relationship -- Fiction; Raccoons -- Fiction; School stories; Separation anxiety in children -- Fiction; Picture books for children